(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
Is not it time to, first, identify and promotes the future senior management by values and patterns of behavior to then train and develop them by knowledge and skills? The present paper, first, start with the need of questioning the current assumptions in which business management rests, placing emphasis in the relevance of behavior`s top managers when these have to face situations of extreme difficulty or moral dilemma. Second, it is made reference to the difficulty that top managers experience to learn from their errors when they face such situations of extreme difficulty or moral dilemma, owing to that it requires them to be identify as exemplary leaders going out of their comfort zone. These leaders decided to go out of such zone and to take responsibility of their decisions when they had to face management difficult situations or/and moral dilemmas that emerged to them by the evolution of their organizations. Four, the author has identified and organized a model with eight of the most relevant dilemmas, providing evidences of how those were resolved by different top business managers and owners and what values they gave priority to guarantee the viability of their organizations. Finally, it is suggested the necessity for filling top management positions, primary, of being based on values to recruit and to promote and, afterwards, being based on competences to train and to develop.